Inflation forecast-based-rules and indeterminacy: a puzzle and a resolution - Paul Levine; Peter McAdam; Joseph G. Pearlman (European Central Bank (ECB), 2006)
We examine an interesting puzzle in monetary economics between what monetary authorities claim (namely to be forward-looking and pre-emptive) and the poor stabilization properties routinely reported for forecast-based rules. Our resolution is that central banks should be viewed as following `Calvo-type' inflation-forecast-based (IFB) interest rate rules which depend on a discounted sum of current and future rates of inflation. Such rules might be regarded as both within the legal frameworks, and potentially mimicking central bankers' practice. We find that Calvo-type IFB interest rate rules are first: less prone to indeterminacy than standard rules with a finite forward horizon. Second, for such rules in difference form, the indeterminacy problem disappears altogether. Third, optimized forms have good stabilization properties as they become more forward-looking, a property that sharply contrasts that of standard IFB rules. Fourth, they appear data coherent when incorporated into a well-known estimated DSGE model of the Euro-area.
Keywords: E52; E37; E58; 330; Calvo-type interest rate rules; indeterminacy; Inflation-forecast-based interest rate rules; Geldpolitik; Inflationserwartung; Zinspolitik; Theorie